The beneficial effects of neutrophil elastase inhibitor on gastrointestinal dysfunction in sepsis - Jia‐Kui Sun; Jing‐Jing Li; Yi‐Hang Deng; Xiang Yin; Xiao‐Tian Huangfu; Zi‐Yu Ye; Xue‐Hui Zhou; Yong‐Ming Chen; Shou‐Tao Yuan; Xiang Wang (Wiley, 2024)
Abstract To investigate the effects of neutrophil elastase inhibitor (sivelestat sodium) on gastrointestinal function in sepsis. A reanalysis of the data from previous clinical trials conducted at our center was performed. Septic patients were divided into either the sivelestat group or the non‐sivelestat group. The gastrointestinal dysfunction score (GIDS), feeding intolerance (FI) incidence, serum levels of intestinal barrier function and inflammatory biomarkers were recorded. The clinical severity and outcome variables were also documented. A total of 163 septic patients were included. The proportion of patients with GIDS ≥2 in the sivelestat group was reduced relative to that in the non‐sivelestat group (9.6% vs. 22.5%, p = 0.047) on the 7th day of intensive care unit (ICU) admission. The FI incidence was also remarkably reduced in the sivelestat group in contrast to that in the non‐sivelestat group (21.2% vs. 37.8%, p = 0.034). Furthermore, the sivelestat group had fewer days of FI [4 (3, 4) vs. 5 (4-6), p = 0.008]. The serum levels of d‐lactate (p = 0.033), intestinal fatty acid‐binding protein (p = 0.005), interleukin‐6 (p = 0.001), white blood cells (p = 0.007), C‐reactive protein (p = 0.001), and procalcitonin (p < 0.001) of the sivelestat group were lower than those of the non‐sivelestat group. The sivelestat group also demonstrated longer ICU‐free days [18 (0-22) vs. 13 (0-17), p = 0.004] and ventilator‐free days [22 (1-24) vs. 16 (1-19), p = 0.002] compared with the non‐sivelestat group. In conclusion, sivelestat sodium administration appears to improve gastrointestinal dysfunction, mitigate dysregulated inflammation, and reduce disease severity in septic patients.